Simulation test of automotive constant velocity joint (CVJ) using computer aided engineering software - Muhammad Zaki, Zainal (2008)
This thesis deals with simulation test of constant velocity joint (CVJ) using computer aided engineering software. The objective of this thesis is to investigate and analyze the stress distribution of CVJ using CAE software. The thesis describes the finite element analysis techniques to predict the failure region on the CVJ and to identify the critical locations of the components. The structural three-dimensional solid modeling of CVJ was developed using the computer-aided drawing software, SolidWork. The strategy of validation of finite element model was developed. The finite element analysis was then performed using CosmosWork. The finite element model of the components was analyzed using the static stress with linear material model approaches. Finally, the stress distribution obtain from the result of analysis are employed as input for the failure region. From the results, it is observed that the analysis using CosmosWork can predict the failure region under fatigue loading. The acquired results tell the failure region occurred at the inner ball hub where it was attach to the shaft and the concentration of the stress occur at that place.